Ongoing regime shift on subarctic Disko Island, Greenland - Emilia Tuomaala; Hui Zhang; Teemu Juselius-Rajamäki; Sanna Piilo; Susanna Salminen-Paatero; Minna Väliranta (Arctic, Antarctic, and Alpine Research)
Significant amounts of soil organic carbon (SOC) are stored in high-latitude soils and are greatly impacted by climate change. Here, we studied soil profiles collected from Disko Island, Greenland, to investigate recent regime shifts, including organic soil initiation and expansion. Our results show newly initiated (age <1950) organic soils overlying the mineral soils in new areas or expansion of older organic soils. We also found signs of vegetation shift in which Sphagnum mosses have become established on sedge habitats. These changes could be linked with the recent warming and longer growing seasons. Both regime shifts have implications for SOC storage, and SOC stock analyses further suggested that, considering their young age and thin organic layer, our sites may store equivalent amounts of carbon or even more than previous studies have found in the area. If conditions for organic soil accumulation continue to improve, our sites may form significant future carbon sinks and stores.